2018
DOI: 10.1590/1983-40632018v4851416
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the spray drift of 2,4-D in tomato using hydraulic nozzles with air induction and LI-700 adjuvant

Abstract: The drift of hormonal effect herbicides is a major problem for agriculture, because, even in small amounts, it may cause high losses in crops with plants that are sensitive to their action mechanism. This study aimed to evaluate the efficiency of hydraulic spray nozzles with air induction, as well as the use of the LI-700 adjuvant, in the reduction of the 2,4-D herbicide drift, in tomato crop. A complete randomized split-plot experimental design, with eight replications, was used. Two herbicide solutions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Differences begin to occur in the middle third of the canopy (Table 3), in which the adjuvant LI700® again demonstrates the highest relative dispersion associated with the highest number of drops that resulted in the highest VMD, again classifying the droplets as ultra coarse. In the assessment of the quality of application with four different types of nozzle, applying a solution with LI700®, GODINHO JUNIOR et al (2018) point a decrease in the risk of drift, thus avoiding losses to the environment. Such circumstances are related to the droplet size, the higher droplet density, and volume of deposited solution, which probably generated a higher droplet coverage rate in the leaf mass, which also corroborates the research of CUNHA & PERES (2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences begin to occur in the middle third of the canopy (Table 3), in which the adjuvant LI700® again demonstrates the highest relative dispersion associated with the highest number of drops that resulted in the highest VMD, again classifying the droplets as ultra coarse. In the assessment of the quality of application with four different types of nozzle, applying a solution with LI700®, GODINHO JUNIOR et al (2018) point a decrease in the risk of drift, thus avoiding losses to the environment. Such circumstances are related to the droplet size, the higher droplet density, and volume of deposited solution, which probably generated a higher droplet coverage rate in the leaf mass, which also corroborates the research of CUNHA & PERES (2010).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, in the middle third, droplets were above coarse, which requires care in the application and corroborates MOTA & ANTUNIASSI (2013), in which study the use of adjuvants increases the volume median diameter during spraying, which requires knowledge in the preparation of the solution, as droplet size and density are related to the poisoning of the plant. In greater droplets, GODINHO JUNIOR et al (2018) have found poisoning of the plant, which requires a decrease in the dose of the product.…”
Section: Resultsmentioning
confidence: 99%
“…The adjuvant Lecithin is a mixture of phosphatidylcholine and propionic acid, commonly used to decrease drift, due to the presence of propionic acid also causes a reduction in the pH of the spray solution. In a study carried out with the herbicide 2,4-D, it was found that the addition of this adjuvant, regardless of the tip model used, reduced the herbicide drift by 4.9% 32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, at the highest application rate used, the average of this characteristic was only 2.83 drops per cm -2 , demonstrating that the increment in the application rate alone was not enough to obtain significant improvements in the coverage of the abaxial surface of the leaves. Studies have shown that air-assisted applications along the spray bar reported improvements in spray levels on the abaxial surface of the lower leaves (Baio et al, 2016;Godinho Júnior et al, 2018). This suggests that the distribution of the spray applied to the abaxial surface of the leaves requires optimization of the application technology, combining the result of a set of factors.…”
Section: /10mentioning
confidence: 99%